The Influence Of Service Quality On Customer Satisfaction At The Local Water Company Of Makassar City In Tamalanrea District - Islam, Fausia; Bakhtiar, Bakhtiar; Rukmana, Novayanti Sopia (Universitas Negeri Makassar, 2025)
This study aims to find out how the influence of service quality on customer satisfaction at the Regional Public Water Company of Makassar City in the District of Tamalanrea. This research uses quantitative research methods. Data collection techniques carried out are through observation, literature, questionnaires, and documentation. The sample used in this study was 100 consumers of the Makassar Municipal Public Water Company in the Tamalanrea District. The data obtained from the research results were processed using data analysis and using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential statistical analysis. The results showed that the variables of service quality and customer satisfaction at PERUMDA Water Supply Makassar City have a significant influence. This was proven based on the results of a simple linear regression test and a correlation coefficient test of 0.664 which means that the relationship between service quality and customer satisfaction is strong. The determinant coefficient ???? ???? is obtained for 0.441 which means that the effect of service quality on consumer satisfaction at PERUMDA Water Supply Makassar City in Tamalanrea District obtains a value of 44.1%, while the remaining 55.9% is influenced by other factors Keywords : Service Quality, Consumer Satisfaction.